Cancer therapeutic implications of microRNAs in the regulation of immune checkpoint blockade - Yan Zhang; Toshihiko Tanno; Chrysi Kanellopoulou (ExRNA)
Abstract Dampening of patients’ immune response to tumor-specific antigens is a major reason for tumor development and progression. Within tumor microenvironment, aberrant expression of immune checkpoints changes T lymphocyte activity, and induces immune tolerance or escape. Inhibiting these checkpoints, called immune-checkpoint blockade, causes the re-activation of the immune response to suppress tumor progression. microRNAs (miRNAs) are small non-coding RNAs that regulate multiple biological processes including carcinogenesis. miRNAs directly and indirectly control the expression of checkpoint receptors and can benefit the immune checkpoint blockade. In this review, we summarize what is known about miRNAs that regulate the expression of various immune checkpoints in cancer therapy and discuss the clinical implications that miRNAs could be useful therapeutic partners assisting the immune checkpoint therapy.